KONTESTASI PANDANGAN BUDAYA DALAM SEJARAH KONGRES KEBUDAYAAN DI INDONESIA: Studi Analisis Teks pada Sebelas Makalah Kongres Kebudayaan di Indonesia Tahun 1991 - Hendi Roy (Saskara : Indonesian Journal of Society Studies, 2021)
This study aims to explain how the contestation of cultural views that occurred at the 1991 Indonesian Cultural Congress. This study uses a qualitative method with a literature study approach and cultural analysis techniques in the text. The text will also be analyzed with the sociological theory of culture according to Raymond Williams to see the process of production and reproduction of culture in the text. The researcher used eleven texts from a total of eighty-nine texts. This study concludes that the contestation of views can be seen based on three characteristics, namely related to the discourse of national development, the modernization of Indonesian culture, and the role of culture in the sector of community life. The relationship between the congress and national cultural politics was shown by the existence of ideas that supported the New Order cultural discourse and criticized it. The 1991 Indonesian Cultural Congress legitimized the national cultural politics of the New Order based on the role of the Directorate of Culture and TMII, the interpretation of undeveloped social formations of society, and the mode of production with a capitalist system. As a tradition that has been carried out in every history of cultural development, congress has always reproduced the values ​​of cultural democratization. Ideas that legitimize the New Order's national cultural politics are exemplified in the cultural papers of Barnabas Suebu, Wayan Geriya, Soemitro, Tilaar, and Sutan Takdir. Meanwhile, those who criticized or rejected the idea were Nirwan Dewanto, W.S. Rendra, Y.B. Mangunwijaya, Umar Kayam, Dawam Rahardjo, and Arief Budiman. Keywords: culture, cultural congress, new order, text analysis, national cultural politics.